2018
DOI: 10.4103/ejd.ejd_266_17
|View full text |Cite
|
Sign up to set email alerts
|

Comparative evaluation of salivary malondialdehyde levels as a marker of lipid peroxidation in early childhood caries

Abstract: Objective:The aim of this study was to evaluate the association between lipid peroxidation and dental caries in children with ECC by estimating the levels of MDA in saliva of children.Materials and Methods:A total of 150 children were selected; 75 children with ECC and 75 children without caries (non-ECC). Saliva samples were collected and centrifuged at 12,000 rpm for 24 min at 4°C to obtain a supernatant. MDA levels were estimated by Buege and Aust method by using thiobarbituric acid. The data obtained were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
115
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 127 publications
(119 citation statements)
references
References 27 publications
4
115
0
Order By: Relevance
“…In addition, multivariate linear regression shows that caries severity is the variable associated with salivary oxidative damage. Taken together, our data demonstrate that carious lesion progression reduces salivary oxidative damage [39,40].…”
supporting
confidence: 69%
See 1 more Smart Citation
“…In addition, multivariate linear regression shows that caries severity is the variable associated with salivary oxidative damage. Taken together, our data demonstrate that carious lesion progression reduces salivary oxidative damage [39,40].…”
supporting
confidence: 69%
“…Our results corroborate previously obtained data showing that the TBARS concentration in saliva of children with E-SCC (0.0019 μmol/L/mg of protein) is lower than in saliva of caries-free children (0.0039 μmol/L/mg of protein). However, recent studies [39,40] have reported controversial results: salivary TBARS concentrations in children aged six years and in patients aged 15-19 years with caries lesions (0.26 μmol/L and 0.71 nmol/mL, respectively) are increased as compared to caries-free patients. Methodological differences may account for the discrepancies between our results and literature data.…”
Section: Discussionmentioning
confidence: 97%
“…Fluoridated toothpaste should be used which removes dental plaque effectively thereby decreasing the incidence of oral disease (Ramakrishnan and Shukri, 2018;Somasundaram, 2015;Subramanyam et al, 2018). A chewable toothbrush can be used instead of the manual toothbrush for effective removal of dental plaque (Packiri, 2017;Christabel, 2015;Govindaraju, 2017).…”
Section: Resultsmentioning
confidence: 99%
“…When pediatric dental patients do not comply with conventional dental treatment, to provide comprehensive and high quality dental treatment, dental practitioners resort to general anesthesia as an aid to the existing treatment modalities (Somasundaram, 2015;Jeevanandan and Govindaraju, 2018;Subramanyam et al, 2018). Physical/mental disability, developmental delay, and acute or chronic disease are potential reasons for noncompliance during the dental appointment.…”
Section: Introductionmentioning
confidence: 99%